(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
It is known that small and medium-sized businesses are an important component of the economic system. This type of business contributes significantly to the economic growth of countries, as it plays a crucial role in ensuring social and economic stability, creating jobs, enhancing competition, and developing innovations. Small and medium-sized businesses also have several advantages and unique characteristics compared to large enterprises. Representatives of small and medium-sized businesses operate through small-scale production, services, and trade, creating many new jobs and significantly contributing to the development of local production.